Studying Some Chemical indicators And Biological Compounds Of Fresh Wild Prunus Fruit )Prunus. spinosa( And its Products Made In Traditional Way (Damascus University Journal of agriculture sciences, 2021)
AbstractThis study was carried out in Department of Food Science in Agricultural College, Damascus University, in 2017 season, which included four different wild Prunus (Prunus. spinoa) products (fresh Prunus, Prunus jam, dried Prunus and concentrated Prunus juice), in order to study the effect of processing on some chemical indicators (total sugars, pH, moisture and acidity as malic acid), content of bioactive compounds (total phenols and  vitamin C) and antioxidant activity according as DPPH for wild Prunus products made in traditional way.Results reveal that there were differences in the percentage of moisture, acidity, total sugar, pH and total soluble solid between processed Prunus products. Also, the results showed that wild Prunus jam had more total sugars (63.75 g/100 g dry weight) and TSS (55 Brix), while concentrated Prunus juice samples exhibited a noticeable increase in content of total phenols (2000.95 mg/100 g dry weight), vitamin C (17.15 mg/100 g dry weight). The Antioxidant activity values assessed by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay varied and differed between processed products, which dried Prunus fruits revealed elevated antioxidation (65.64%), followed by Prunus jam samples (56.52%), and final the concentrated Prunus juice samples (50.49%). Thus, Wild Prunus (Prunus. spinosa) is considered a healthy food rich in antioxidants.
Keywords: Prunus. spinosa, Jam; Chemical Indicators